Islam-Yahudi: Bisakah Berdamai? - Fergina, Ana; Hasaruddin, Hasaruddin; Syukur, Syamzan (Jurnal Alwatzikhoebillah : Kajian Islam, Pendidikan, Ekonomi, Humaniora, 2024)
Relations between Judaism and Islam have existed since the time of the Prophet until now. This relationship underwent a very drastic change. This article examines the relationship between Islam and Judaism from the time of the Prophet until now and the attitude of Muslims towards this conflict. This article uses a descriptive approach with a literature review as a data collection tool. The finding shows that the relationship between Islam and Judaism is intertwined through political, economic, and theological relations. Political interests, namely regional power, promoted the conflict between Muslims and Jews. As Muslims, unity and brotherhood between Muslims must be further enhanced to achieve peace in Palestine immediately. Muslims must instill in their souls that Palestine is a matter of Islamic faith. This article needs to explain in detail the development of relations between Islam and Judaism in the 20th century. Therefore, continued research is essential to improve this article.